2016
DOI: 10.1111/1750-3841.13331
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Purification of Quercitrin, Hyperoside, Rutin, and Afzelin from Zanthoxylum Bungeanum Maxim Leaves Using an Aqueous Two‐Phase System

Abstract: In this study, an aqueous two-phase system (ATPS) based on ethanol/NaH2 PO4 was developed for the extraction and purification of quercitrin, hyperoside, rutin, and afzelin from Zanthoxylum bungeanum Maxim leaves. These 4 flavonoids were 1st extracted from dried Z. bungeanum leaves using a 60% ethanol solution and subsequently added to the ATPS for further purification. The partition behavior of the 4 flavonoids in ATPS was investigated. The optimal ATPS conditions were: 29% (w/w) NaH2 PO4 , 25% (w/w) ethanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Under the optimum conditions, the contents of the four main flavonoids in the purified products were approximately two to three times higher than those in the crude extracts, and the antioxidant activity significantly increased after UAE and MAR treatment. In addition, compared with our previous study (He et al, 2016) of aqueous 2-phase extraction (ATPE), it was found that the four main flavonoids were enriched significantly and that the antioxidant activities were obviously improved compared with ATPE. In the end, the procedures of separation used in this study are simple, highly efficient, environmentally friendly, low cost and easy to scale up.…”
Section: Resultsmentioning
confidence: 56%
“…Under the optimum conditions, the contents of the four main flavonoids in the purified products were approximately two to three times higher than those in the crude extracts, and the antioxidant activity significantly increased after UAE and MAR treatment. In addition, compared with our previous study (He et al, 2016) of aqueous 2-phase extraction (ATPE), it was found that the four main flavonoids were enriched significantly and that the antioxidant activities were obviously improved compared with ATPE. In the end, the procedures of separation used in this study are simple, highly efficient, environmentally friendly, low cost and easy to scale up.…”
Section: Resultsmentioning
confidence: 56%
“…The content of hyperoside, the most abundant fl avonol glycoside (4.54-2.68 mg/g dry weight), decreased from May to August, and then slightly increased in September. This increase in the content of hyperoside may be related to a drop in temperature [He et al, 2016].…”
Section: Variation In the Content Of Individual Phenolic Compounds Dumentioning
confidence: 94%
“…[ 13 ] The flavonoids were mainly composed of quercitrin, hyperoside, rutin, and afzelin and displayed free radical scavenging activity. [ 40 ] The alkamide fraction, identified as the tingling principles of this plant, was rich in α-sanshool, hydroxy-β-sanshool, and hydroxy-γ-sanshool and displayed anti-itching and anti-wrinkles activities. [ 41 ] Yang et al .…”
Section: Discussionmentioning
confidence: 99%